Development and characterization of an aircraft inlet system for broader quantitative particle sampling at higher altitudes: aerodynamic lenses, beam and vaporizer diagnostics, and pressure-controlled inlets - D. Kim; D. Kim; P. Campuzano-Jost; P. Campuzano-Jost; H. Guo; H. Guo; D. A. Day; D. A. Day; D. Yang; D. Yang; D. Yang; S. Dhaniyala; et al. (Aerosol Research, 2025)
Field-deployable real-time aerosol mass spectrometers (AMSs) typically use an aerodynamic lens as an inlet that collimates aerosols into a narrow beam over a wide range of particle sizes. Such lenses need constant upstream pressure to work consistently. Deployments in environments where the ambient pressure changes, e.g., on aircraft, typically use pressure-controlled inlets (PCIs). These have performed less well for supermicron aerosols, such as the larger particles in stratospheric air and some urban hazes. In this study, we developed and characterized a new PCI design (“CU PCI-D”) coupled with a recently developed PM2.5 aerodynamic lens, with the goal of sampling the full accumulation mode of ambient aerosols with minimal losses up to upper troposphere and lower stratosphere (UTLS) altitudes. A new computer-controlled lens alignment system and a new 2D particle beam imaging device that improves upon the Aerodyne aerosol beam width probe (BWP) have been developed and tested. These techniques allow for fast automated aerosol beam width and position measurements and ensure the aerodynamic lens is properly aligned and characterized for accurate quantification, in particular for small sizes that are hard to access with monodisperse measurements. The automated lens alignment tool also allows position-dependent thermal decomposition to be investigated on the vaporizer surface. The CU PCI-D was tested on the TI3GER campaign aboard the NCAR/NSF G-V aircraft. Based on comparisons with the co-sampling UHSAS particle sizer, the CU aircraft AMS with the modified PCI consistently measured ∼ 89 % of the accumulation-mode particle mass in the UTLS.